The anticancer compound dolichol from Ceriops tagal and Rhizophora mucronata leaves regulates gene expressions in WiDr colon cancer - Istiqomah, Meighina Atika; Hasibuan, Poppy Anjelisa Zaitun; Nuryawan, Arif; Sumaiyah Sumaiyah,; Siregar, Etti Sartina; Mohammad Basyuni, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Mangrove plants produce polyisoprenoid alcohol. The polyisoprenoid consists of polyprenol and dolichol, which in pharmacological activity act as anticancer agents. The major polyisoprenoid compound of mangrove plants Ceriops tagal and Rhizophora mucronata was reported as dolichol. The present study was conducted to examine the anticancer effects of dolichol from C. tagal and R. mucronata leaves on WiDr cells and cell cycle-related cancer for 24 h and to evaluate the regulation of five genes, p53, EGFR, PI3K, Akt, and mTOR. The inhibited cell cycle was analysed by flow cytometry and the gene expression of p53, EGFR, PI3K, Akt, and mTOR was determined using reverse transcriptionpolymerase chain reaction (RT-PCR) method. Dolichol from C. tagal was more effective than that from R. mucronata, where it worked on the G0/G1 cycle for 87.94% and 82.36%, respectively, and regulated positive control 5-FU on the G0/G1 cycle (88.12%), S (9.52%) and G2-M (6.42%). The upregulation (p53) and downregulation (EGFR) contributed to the contracting cell cycle of colon cancer cells (WiDr) in PI3K, Akt and mTOR genes. To summarise, the current study suggests significant pharmacological properties of dolichols in C. tagal and R. mucronata leaves, which worked explicitly in the G0/G1 phase.